Effect of pressure on structural, electronic dispersion relations, optical and thermoelectric properties of CsNbO3 perovskite for photovoltaic and energy applications. (15th January 2023) - Fadhali, Mohammed M.; Bakar, Abu; Ali, Saif; Afaq, A.; Hegazy, H.H.
Graphical abstract: Abstract: The perovskites have not only been recognized for memory devices and spintronic applications but are equally important for the thermoelectric response calculations. In this research work, the effect of pressure on structural, electronic dispersion curves, optical and thermoelectric parameters of CsNbO 3 cubic perovskite have been investigated by using the pseudopotential approach alongside the Boltzmann transport theory. The CsNbO 3 was reported stable in simple cubic structure by means of energy-volume optimization and phonon dispersion curves by B. Sabir et. al. CsNbO 3 is reported as the direct band gap semiconductor with band gap around 1.95 eV at ambient pressure. Interestingly the band gap decrease with the increase in the pressure. The absence of negative phonon frequency shows the dynamical stability of this material under pressure. The analysis of imaginary part of dielectric response function predicts the utility of this perovskite in high frequency microwave sensors as well as the optoelectronic devices like optical sensors and interconnects. Further, the thermoelectric parameters such as Seebeck coefficient (S), electronic part of thermal conductivity ( κe /τ ), electrical conductivity ( σ/τ ) and power factor (PF) have been discussed within a specific temperature and pressure range (300–1200 K) and (10–50 GPa) respectively. The calculated values of power factor and optical constants prove it a potential candidate for thermoelectric and photovoltaic applications.